Developing a Learner-Centered Curriculum for a Rural Public Health Program - Njoku, Anuli; Wakeel, Fathima; Reger, Michael; Jadhav, Emmanuel; Rowan, Julie (International Journal of Teaching and Learning in Higher Education, 2017)
Rural communities, compared with their urban counterparts, have higher rates of disease and adverse health conditions, fueling disparities in health outcomes. This encourages the need for effective curricula to engage students and enable them to address such disparate health outcomes as imminent health professionals. Incorporating learner-centered teaching strategies, such as collaboration and power-sharing, into public health (PH) courses can enhance student learning and help faculty enable future health professionals to address needs of rural, underserved populations. Successfully engaging students to explore issues related to rural health disparities in their education, research, and training can thereby advance PH practice. This paper describes the collaborative efforts of five PH faculty, an instructional designer, and administrators to develop a learner-centered curriculum for a newly launched PH program in a rural Midwestern United States (US) university.
Keywords: Audience Response Systems; College Faculty; Course Descriptions; Disadvantaged; Diseases; Health Personnel; Instructional Design; Program Descriptions; Program Development; Public Health; Rural Areas; Student Centered Curriculum; Teacher Collaboration; Teaching Methods; Workshops; dept.pch